2012
DOI: 10.1111/j.1755-263x.2012.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing mutualism between humans and wild fauna: insights from vultures as ecosystem services providers

Abstract: In parallel with economic and social changes, mutualism in human-vulture relations has virtually disappeared worldwide. Here, we describe the mutualistic relationship between humans and the globally threatened Egyptian vulture in Socotra, Yemen. By analyzing both the spatial distribution of vultures and the amount of human byproducts they consume, we show that human activities enable the maintenance of the densest population of this rare scavenger, whereas vultures provide a key regulating service by disposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 27 publications
1
90
0
1
Order By: Relevance
“…This reinforces the call for improved integration of socio-economic approaches to urban ecology, which will often require a reconceptualization of humans and their activities (Pickett et al 2001;Grimm et al 2008;Esbjorn-Hargens and Zimmerman 2009;Warren and Lepczyk 2012). Furthermore, the high predictive power of our logistic model of nest-site selection highlighted the importance of habitat models as potential conservation tools for urban planning (for integration of modelling and conservation in urban settings, see examples and reviews in Gordon et al 2009;Kowarik 2011;Lerman et al 2014). Overall, our model suggested that Delhi Black Kites selected several socio-ecological features at multiple scales, from local tree-arrangement, to neighbourhood-level landscape structure, to the larger-scale spatial zoning of access to subsidies provided by human socio-religious practices (see below).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This reinforces the call for improved integration of socio-economic approaches to urban ecology, which will often require a reconceptualization of humans and their activities (Pickett et al 2001;Grimm et al 2008;Esbjorn-Hargens and Zimmerman 2009;Warren and Lepczyk 2012). Furthermore, the high predictive power of our logistic model of nest-site selection highlighted the importance of habitat models as potential conservation tools for urban planning (for integration of modelling and conservation in urban settings, see examples and reviews in Gordon et al 2009;Kowarik 2011;Lerman et al 2014). Overall, our model suggested that Delhi Black Kites selected several socio-ecological features at multiple scales, from local tree-arrangement, to neighbourhood-level landscape structure, to the larger-scale spatial zoning of access to subsidies provided by human socio-religious practices (see below).…”
Section: Discussionmentioning
confidence: 86%
“…However, for many urban species, the attraction to an extreme anthropogenic ecosystem is based on the exploitation of human provision itself rather than resilience to its actions, and for some synanthropic species this may derive from millennia of co-existence with man, better seen as an integral portion of their niche as well as a beneficiary of ecosystem services (e.g. Marzluff and Angell 2005;Gangoso et al 2013). In our system, Delhi kites cannot be thought of in isolation from humans and their voluntary and involuntary subsidies, which would qualify them as anthropophilic and anthropodependent species (sensu Hulme-Beaman et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, vultures contribute to the disposal of human byproducts (urban organic waste ;Gangoso et al 2013) and carcasses of livestock and wild animals, thereby preventing the spread of diseases, such as ebola, anthrax, rabies . Vultures were also found to contribute to reduced green-house-gas emissions by limiting transportation needed to transfer byproducts (Morales-Reyes et al 2015).…”
Section: Introductionmentioning
confidence: 99%